Bridging Universals and Relativity: An Analysis of Syntax, Cognitive Influence, and Cultural Variation in Linguistic Theory (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2024)
This research explores the intersection of syntax with theories of linguistic universals, linguistic relativity, and the cognitive architecture of language. Beginning with an examination of Greenberg’s approach to linguistic universals, the study delves into Chomsky’s transformational grammar, focusing on the principles of deep and surface structures to understand the universality of syntactic rules across languages. Through this lens, the research investigates how Greenberg’s universals support the idea of shared syntactic patterns and compares these insights with Chomsky’s generative framework. Lakoff’s cognitive critique of Chomsky’s formalist approach is discussed, highlighting the cognitive dimensions of syntax and questioning the rigidity of transformational grammar. Additionally, the study considers Fodor’s Language of Thought hypothesis (LOT), which proposes that thought itself may possess a syntax-like structure, potentially bridging syntax and mental representation. Extending into the Sapir-Whorf hypothesis, the research examines linguistic relativity’s assertion that language influences thought, thus connecting syntactic structure with cognitive and cultural perception. Together, these perspectives offer a multidisciplinary view that links syntax with cognitive and semantic domains, suggesting that while syntax may possess universal principles, it also interacts dynamically with thought and perception across diverse linguistic and cultural contexts.